Pengaruh Product Quality Dan Brand Image Terhadap Customer Loyalty Dengan Study Pustaka: Indonesia - shifa megarani shifa megarani; Muinah Fadhilah Muinah Fadhilah (JOURNAL SAINS STUDENT RESEARCH, 2024)
This study aims to analyze the effect of product quality and brand image on customer loyalty with the literature study method. The data uses secondary data from journals, books, and the internet. From previous research, it shows that if it significantly affects product quality and brand image on customer loyalty. The implication is that further research can add several variables that influence customer loyalty factors.